Improving cold-adaptability of mesophilic cellulase complex with a novel mushroom cellobiohydrolase for efficient low-temperature ensiling. (May 2023) - Gong, Ming; Wang, Ying; Bao, Dapeng; Jiang, Shan; Chen, Hongyu; Shang, Junjun; Wang, Xiaojun; Hnin Yu, Hnin; Zou, Gen
Graphical abstract: Highlights: Low temperature severely limits rice straw-silage processing. Novel cold-active cellobiohydrolase Vv CBHI-I from V. volvacea was isolated. Vv CBHI-I exhibited outstanding cellobiohydrolase activity at 10–30 °C. Vv CBHI-I greatly improved saccharification efficiency of cellulase complex at 10 °C. A flexible structure and fewer disulfide bonds explain Vv CBHI-I cold acclimation. Abstract: Low ambient temperature poses a challenge for rice straw-silage processing in cold climate regions, as cold limits enzyme and microbial activity in silages. Here, a novel cold-active cellobiohydrolase ( Vv CBHI-I) was isolated from Volvariella volvacea, which exhibited outstanding cellobiohydrolase activity at 10–30 °C. The crude cellulase complex in the Vv CBHI-I-expressing transformant T1 retained 50% relative activity at 10 °C, while the wildtype Trichoderma reesei showed <5% of the activity. Vv CBHI-I greatly improved the saccharification efficiency of the cellulase complex with pretreated rice straw as substrate at 10 °C. In rice straw silage, pH (<4.5) and lactic acid content (>4.6%) remained stable after 15-day ensiling with the cellulase complex from T1 and Lactobacillus plantarum . Moreover, the proportions of cellulose and hemicellulose decreased to 29.84% ± 0.15% and 21.25% ± 0.26% of the dried material. This demonstrates the crucial potential of mushroom-derived cold-active cellobiohydrolases in successful ensiling in cold regions.